(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Digital fitting system is a virtual fitting system based on computer and internet technology. The aim of the research, described in this paper, is to share fundamental knowledge surrounding the development of digital fitting system. In addition, we present data, collected from 1050 questionnaires completed by both the consumers and managers in 10 cities of China, in order to analyze the requirements for digital fitting system in China. On this basis of this work, we conclude with some advice regarding the building of digital fitting systems.